IGS sequences in Cestrum present AT- and GC-rich conserved domains, with strong regulatory potential for 5S rDNA - de Souza, Thaíssa Boldieri; Gaeta, Marcos Letaif; Martins, Cesar [UNESP]; Vanzela, André Luís Laforga (Springer Nature, 2020)
The 35S and 5S ribosomal DNA (rDNA) organized in thousands of copies in genomes, have been widely used in numerous comparative cytogenetic studies. Nevertheless, several questions related to the diversity and organization of regulatory motifs in 5S rDNA remain to be addressed. The 5S rDNA unit is composed of a conserved 120 bp length coding region and an intergenic spacer (IGS) containing potential regulatory motifs (Poly-T, AT-rich and GC-rich) differing in number, redundancy and position along the IGS. The Cestrum species (Solanaceae) have large genomes (about 10 pg/1C) and conserved 2n = 16 karyotypes. Strikingly, these genomes show high diversity of heterochromatin distribution, variability in 35S rDNA loci and the occurrence of B chromosomes. However, the 5S rDNA loci are highly conserved in the proximal region of chromosome 8. Comparison of seventy-one IGS sequences in plants revealed several conserved motifs with potential regulatory function. The AT- and GC-rich domains appeared highly conserved in Cestrum chromosomes. The 5S genic and the GC-rich IGS probe produced FISH signals in both A (pair 8) and B chromosomes. The GC-rich domain presented a strong potential for regulation because it may be associated with CpG islands organization, as well as to hairpin and loop organization. Another interesting aspect was the ability of AT- and GC-rich motifs to produce non-heterochromatic CMA/DAPI signals. While the length of the 5S rDNA IGS region varied in size between the Cestrum species, the individual sequence motifs seem to be conserved suggesting their regulatory function. The most striking feature was the conserved GC-rich domain in Cestrum, which is recognized as a signature trait of the proximal region of chromosome pair 8.
Keywords: AT-rich domains; B chromosomes; Cestreae; Chromosome banding; FISH; GC-rich domains; Poly-T; rDNA sequences